Assessment of functional efficiency different ways to recovery system digestive after gastrectomy - A. G. Baryshev; N. V. Hachaturyan; D. A. Valyakis; A. O. Lysenko; Yu. S. Kalyncheva; M. V. Bodnya (Инновационная медицина Кубани, 2019)
The article analyzes the functional results of the digestive system after a sweat gastrectomy for gastric cancer. A comparison of the frequency of postoperative complications functionality, characteristics of carbohydrate and protein metabolism in patients after gastrectomy with extended (D2) and standard (D1) lymph node dissection using well-known methods and developed by the authors loop ezofagenterostomii and reservoir jejunogastroplasty.